The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1159/000177040
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation and Triggers of Cardiovascular Disease

Abstract: It has recently been shown that approximately 90% of cases of non-fatal myocardial infarction and many cases of sudden cardiac death are caused by disruption of a coronary atherosclerotic plaque, followed by occlusive thrombus formation. Secondly, the circadian pattern of myocardial infarction is well known to feature a prominent increase in the morning hours. Taken together, these factors may provide an opportunity to reduce deaths caused by cardiovascular disease. Findings indicate that, in many cases, plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
1
12
0
4
Order By: Relevance
“…Conversely, a dynamic system may also be disadvantageous. For example, excessive surges in sympathetic activity, with concurrent vagal withdrawal is associated with the waking process [15], and these changes may account for the increased occurrence of adverse cardiac events towards the end of the sleep period and during wakefulness following sleep [20,24,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a dynamic system may also be disadvantageous. For example, excessive surges in sympathetic activity, with concurrent vagal withdrawal is associated with the waking process [15], and these changes may account for the increased occurrence of adverse cardiac events towards the end of the sleep period and during wakefulness following sleep [20,24,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…1 Some believe this morning excess of cardiovascular risk parallels the usual circadian pattern of physical activity, blood pressure, plasma catecholamines, and/or plasma cortisol. [2][3][4][5] Early studies of the timing of acute stroke, however, indicated that many afflicted patients reported awakening with new neurologic deficits, and several reports indicated that acute strokes tended to occur either during the evening hours or during sleep. [6][7][8] This led to the conclusion that especially because acute therapies for stroke-in-evolution were not particularly effective, there was little reason to consider acute stroke as a medical emergency because the onset of symptoms was thought to occur during sleep, when most patients would not recognize them.…”
mentioning
confidence: 99%
“…16 Tolerability was good during both treatment phases and there were no serious adverse events. Similar numbers of patients reported adverse events following amlodipine and lisinopril and there were 95% confidence intervals (CI) relate to differences in mean % changes in BP between treatments;…”
Section: Discussionmentioning
confidence: 91%